Optimalisasi Pemanfaatan Media Online untuk Penyebaran Informasi dalam Upaya Peningkatan Penerapan Pedoman Gizi Seimbang (PGS) dan Ketahanan Pangan di Kota Banjarbaru Provinsi Kalimantan Selatan - Dhea Dasa Cendekia Zairin; Halimah Zatalini; Suhendi Suhendi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Pertanian Bogor, 2021)
The Covid-19 pandemic has a detrimental impact on various sectors of life, including the food and agriculture sectors. The Department of Food Security, Agriculture and Fisheries (DKP3) of Banjarbaru City is the implementing element of government affairs in the Agriculture, Plantation Sector, Fishery Sector, Animal Husbandry Sector, and Extension Sector which is the regional authority. During the Covid-19 pandemic, the role of DKP3 as a food stabilizer was urgently needed considering that this disease outbreak had created obstacles in the distribution of foodstuffs and people's access to various food products. On the other hand, the Large-Scale Social Restrictions (PSBB) policy has made the trend of using social media in the community increase. Therefore, DKP3 can use this trend to be more active in social media as a way of disseminating educational information to the public regarding the use of house yards as a solution to meeting household food needs, alternative sources of additional income, and application of balanced nutrition guidelines for the people of Banjarbaru is expected to be able to survive this pandemic. The activities carried out are the dissemination of information on Balanced Nutrition Guidelines (PGS) and Household Food Security which aims to educate about balanced nutrition guidelines and the importance of household food security by utilizing the household yard. Dissemination of information on Balanced Nutrition Guidelines (PGS) and Household Food Security also aims to increase awareness, knowledge, and skills of the people of Banjarbaru City. Keywords: balanced nutrition guidelines, food security, covid-19